Loneliness and Psychological Distress Before and During the COVID-19 Pandemic: Relationships With Social Media Identity Bubbles - Latikka Rita; Koivula Aki; Oksa Reetta; Savela Nina; Oksanen Atte (Elsevier Ltd., 2022)
Impacts of the COVID-19 pandemic on well-being and mental health are a concern worldwide. This article is based on two longitudinal studies that investigated the role of social media use in loneliness and psychological distress before and during the COVID-19 pandemic. Study 1 utilized nationally representative 3-point longitudinal data (n = 735) collected in 2017–2020 on the Finnish population. Study 2 utilized 5-point longitudinal data (n = 840) collected in 2019–2021 representing the Finnish working population. We analyzed the data using multilevel mixed-effects regression analysis. A longitudinal analysis of Study 1 showed that perceived loneliness did not increase among the Finnish population during the COVID-19 pandemic. Stronger involvement in social media identity bubbles predicted lower loneliness during the pandemic. Study 2 results showed that since the outbreak of the pandemic, psychological distress has increased among lonely individuals but not among the general population. Involvement in social media identity bubbles predicted generally lower psychological distress during the COVID-19 pandemic, but it did not buffer against higher psychological distress among lonely individuals. The findings suggest that perceived loneliness is a risk factor for prolonged negative mental health effects of the pandemic. Social media identity bubbles can offer meaningful social resources during times of social distancing but cannot protect against higher psychological distress among those who perceive themselves as often lonely.